2017
DOI: 10.7554/elife.29738
|View full text |Cite
|
Sign up to set email alerts
|

Human and nonhuman primate meninges harbor lymphatic vessels that can be visualized noninvasively by MRI

Abstract: Here, we report the existence of meningeal lymphatic vessels in human and nonhuman primates (common marmoset monkeys) and the feasibility of noninvasively imaging and mapping them in vivo with high-resolution, clinical MRI. On T2-FLAIR and T1-weighted black-blood imaging, lymphatic vessels enhance with gadobutrol, a gadolinium-based contrast agent with high propensity to extravasate across a permeable capillary endothelial barrier, but not with gadofosveset, a blood-pool contrast agent. The topography of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
521
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 467 publications
(550 citation statements)
references
References 31 publications
24
521
1
4
Order By: Relevance
“…Given our pre- and post-contrast technique, we are able to include for the first time vessel wall and dural foci subtypes, which persist most frequently and their appearance very closely matches recent descriptions of meningeal lymphatics or the glial lymphatics system. 1922 Longitudinal persistence of meningeal enhancement is not significantly different between those on or off immunomodulatory treatment; nor is there a significant difference in rates of longitudinal persistence between those with progressive clinical phenotypes (primary progressive MS and secondary progressive MS) and those without a progressive clinical phenotype (relapsing remitting MS). However, there is a significantly increased number of persistent foci in subjects that have worsening Expanded Disability Status Scale scores at 1 year compared to those that do not, suggesting that persistently enhancing meningeal foci may be an in-vivo imaging marker for ongoing meningeal inflammation causative of clinical progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our pre- and post-contrast technique, we are able to include for the first time vessel wall and dural foci subtypes, which persist most frequently and their appearance very closely matches recent descriptions of meningeal lymphatics or the glial lymphatics system. 1922 Longitudinal persistence of meningeal enhancement is not significantly different between those on or off immunomodulatory treatment; nor is there a significant difference in rates of longitudinal persistence between those with progressive clinical phenotypes (primary progressive MS and secondary progressive MS) and those without a progressive clinical phenotype (relapsing remitting MS). However, there is a significantly increased number of persistent foci in subjects that have worsening Expanded Disability Status Scale scores at 1 year compared to those that do not, suggesting that persistently enhancing meningeal foci may be an in-vivo imaging marker for ongoing meningeal inflammation causative of clinical progression.…”
Section: Resultsmentioning
confidence: 99%
“…Which anatomic/pathologic substrates are represented by vessel wall and dural foci is unknown, but interestingly, both closely match what was recently described for visualization of meningeal lymphatics by FLAIR MRI. 2022 Thus, it is possible that these findings may represent gadolinium absorption by lymphatic structures after leakage into the cerebrospinal fluid. The accumulation of gadolinium signal alongside the outer wall of vessels in the vessel wall pattern is also very reminiscent of the expected location and direction of drainage of solutes from brain parenchyma along the recently described glymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…After intrathecal gadobutrol, via methodology previously proposed by Iliff et al, the signal increase on brain MRI was shown to have a faster distribution than predicted by diffusion alone . More recently, meningeal lymphatic vessels were identified with large similarities in rodents and human subjects . Absinta and colleagues described a system of lymphatic vessels along dural venous sinuses on FLAIR and T1‐weighted black‐blood imaging after intravenous gadobutrol injection, exploiting the lack of blood–meningeal barrier in dural vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the glymphatic pathway was first described in rodents by 2 photon‐microscopy studies, and then measured in the human brain with magnetic resonance imaging (MRI) before and multiple time points after intrathecal injection of a contrast agent (gadolinium) in 2015 . In the same year, a network of true lymphatic vessels within the mammalian dura mater that runs alongside blood vessels was confirmed by 2 independent teams, whereas the existence of MLVs in humans was reported with the visualization of high‐resolution T2–fluid attenuated inversion recovery (FLAIR), T1‐weighted black‐blood imaging in 2017, and confocal microscopy in 2018 …”
mentioning
confidence: 99%